Las fuentes de voz en las redes de banda ancha ATM - Poveda Zafra, José Noé; Betancourt Uscátegui, Álvaro (Ingeniería, 2000)
Modeling voice sources in telematic networks requires increasingly complex mathematical processes. The corresponding models range from simple constant bit rate models to more elaborated Poisson batch arrivals models. In search of efficient resource utilization, we need rigorous mathematical formulation of models that involve different ATM parameters such as length distribution, cell loss probability, cell delay distribution and burst delay distribution. Furthermore, grouping and multiplexing voice cells according to the ON-OFF pattern of a voice conversation require additional parameters such as peak, average and minimum cells rate. This paper focuses on efficient bandwith utilization on an ATM broadband network by multiplexing fluid flow voice sources.